6(-5n+7)-16=-180

Simple and best practice solution for 6(-5n+7)-16=-180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-5n+7)-16=-180 equation:


Simplifying
6(-5n + 7) + -16 = -180

Reorder the terms:
6(7 + -5n) + -16 = -180
(7 * 6 + -5n * 6) + -16 = -180
(42 + -30n) + -16 = -180

Reorder the terms:
42 + -16 + -30n = -180

Combine like terms: 42 + -16 = 26
26 + -30n = -180

Solving
26 + -30n = -180

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + -30n = -180 + -26

Combine like terms: 26 + -26 = 0
0 + -30n = -180 + -26
-30n = -180 + -26

Combine like terms: -180 + -26 = -206
-30n = -206

Divide each side by '-30'.
n = 6.866666667

Simplifying
n = 6.866666667

See similar equations:

| 8.2x-3.7x=-72 | | -1.5r=13.84-18.8r | | 32+1.8c= | | -9xy+xy= | | 2x+2yz=8 | | 15-2=n-1 | | 12m+4=12m+8 | | -20d+1=-3d-18d+13 | | M^2+m-23=-3 | | -24x+2=18-14x | | 6x+15-3=2(x+3) | | -4(8p+8)=-2(6p-8)-4p | | 43-(2c+4)=2(c+7)c | | -5(x-1)=-30 | | 3n-5+2n+12=-3(4x-6) | | 0.8(x-6)=9.6 | | 12x+10*20x=100 | | -5n+10=5n-4 | | -1-18h=-19h+5 | | -8t*3t+2=-5t-6t | | px=20-4qx+2py | | 9(x+8)+x=2(x+5)-4 | | 4(x-3)+2x=36 | | 14+2(4w-3)=40 | | 17u+19=16u | | .5(-4x+3)=5(x-4) | | -9-7g=-4g | | Y+2=-2(x-5) | | 5x(7x-3)=20x | | 9x+3x+99=9x+48 | | 6a+6=14a-14 | | 6a+6=14-14 |

Equations solver categories